Temperature gradients and stress distributions in concrete box-girder bridges during hot-mix asphalt paving. (October 2021) - He, Zhi-Qi; Ma, Zeng; Zhang, Shixiang; Liu, Zhao; Ma, Zhongguo John
Abstract: Thermal actions have frequently been related to the cracking of concrete bridges. During the paving of hot-mix asphalt (HMA) on the bridge deck, a high temperature gradient will generate through the depth of the concrete box-girder, which may cause cracks in the bridge deck. Up to date, little attention has been given to this problem, and little data were available in the literature. This study provides a systematic investigation of thermal actions during HMA paving, through a combination of field monitoring, heat-transfer analyses, and analytical studies. The heat-transfer process and the thermal field characteristics are clarified. Equations are presented to predict the temperature gradient induced by the heat of hot asphalt. After that, an analytical method is proposed to calculate the thermal-induced transverse stresses in the bridge deck. The main findings are as follows: 1) the temperature gradient can be approximated by a natural exponential function, with the point of zero temperature difference 50–60 cm below the top of the deck; 2) the maximum temperature difference is related to several factors, including the thickness of hot asphalt, the temperature of hot asphalt, the initial deck surface temperature, and the thickness of the leveling layer; and 3) during paving of the Jianghai Bridge in summer, the maximum thermal-induced transverse tensile stress in the bottom surface of the top slab is as high as 3.6 MPa, which is three times the wheel-load induced stress.